2016
DOI: 10.1101/pdb.top088849
|View full text |Cite
|
Sign up to set email alerts
|

Overview of CRISPR–Cas9 Biology

Abstract: Prokaryotes use diverse strategies to improve fitness in the face of different environmental threats and stresses, including those posed by mobile genetic elements (e.g., bacteriophages and plasmids). To defend against these elements, many bacteria and archaea use elegant, RNA-directed, nucleic acid– targeting adaptive restriction machineries called CRISPR–Cas (CRISPR-associated) systems. While providing an effective defense against foreign genetic elements, these systems have also been observed to play critic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 165 publications
(338 reference statements)
0
15
0
Order By: Relevance
“…The RecA-like protein fusion successfully imported a restriction enzyme but failed to import Cas9 [ 26 ]. Therefore, we tested the ability of GFPmut1 to import three proteins from different CRISPR-cas systems: Cas3, Cas9, and Cas13 [ 27 31 ]. When fused to sfGFP, all three localized in the cytoplasm, indicating that all three of these proteins are normally excluded from the nucleus ( Fig 5A, 5C and 5E ).…”
Section: Resultsmentioning
confidence: 99%
“…The RecA-like protein fusion successfully imported a restriction enzyme but failed to import Cas9 [ 26 ]. Therefore, we tested the ability of GFPmut1 to import three proteins from different CRISPR-cas systems: Cas3, Cas9, and Cas13 [ 27 31 ]. When fused to sfGFP, all three localized in the cytoplasm, indicating that all three of these proteins are normally excluded from the nucleus ( Fig 5A, 5C and 5E ).…”
Section: Resultsmentioning
confidence: 99%
“…Spacers are transcribed into small RNAs that guide the direct cleavage of viral DNA by Cas nuclease proteins. The immunized population not only acquires resistance to its predators but also passes this resistance mechanism vertically to its progeny [ 42 , 43 ]. In this study, we observed that E. faecalis genomes contain a significantly higher number of recombination hotspots than E. faecium genomes do.…”
Section: Discussionmentioning
confidence: 99%
“…The RecA-like protein fusion successfully imported a restriction enzyme but failed to import Cas9 (26). Therefore, we tested the ability of GFPmut1 to import three proteins from different CRISPR-cas systems: Cas3, Cas9, and Cas13 (2731). When fused to sfGFP, all three localized in the cytoplasm, indicating that all three of these proteins are normally excluded from the nucleus (Fig 5A, C, E).…”
Section: Resultsmentioning
confidence: 99%